Psychoactive substance use among Nigerian secondary school students: a review of current literature - Shuaibu, Hassana Ojonuba; Abdul Rahman, Haliza; Abu Samah, Asnarulkhadi; Mohd Zulkefli, Nor Afiah (Universiti Putra Malaysia Press, 2020)
Substance use is a global health issue that may lead to engagement in other risky behaviours, addiction, accidents and non-communicable diseases. In Nigeria, this risky behaviour is becoming an emerging trend among secondary school students. This review was thus carried out to gain an overview of the prevalence and risk factors of substance use among secondary school students in Nigeria. A literature search of articles in Scopus, PubMed and other online databases was conducted for articles published between 2009 to 2019. Sixteen studies met the inclusion criteria. Overall, psychoactive substance ranged from 21% to 87%. Alcohol consumption was the highest, while the use of tobacco, cannabis, and cocaine was low. The mean age at initiation ranged from 11 to 15 years. Male gender, peer influence, parental factors, individual factors and knowledge on the dangers of psychoactive substance use were common factors associated with substance use among Nigerian secondary school students. School-based interventions should be multifaceted and holistic. More research should be theory-based and conducted in the Northern parts of Nigeria. Future studies should measure other psychological factors that may influence these behaviours to provide more insight into interventions.